Identification of risk factors for hearing impairment in newborns: a hospital based study - Nermin Hrnčić (Medicinski glasnik, 2017)
Aim: To identify risk factors for hearing impairment presented in neonates born in Cantonal Hospital Zenica (CHZ) and to estimate their influence on outcome of hearing tests in Newborn Hearing Screening (NHS). Methods: Retrospective-prospective study was done at the Department of Gynaecology and Maternity. The NHS was performed with transitory evoked otoacoustic emissions (TEOAE) during a six-month period using "Titan" device (Interacoustics, Denmark). The questionnaire was written for the purpose of getting more structured basic information about every newborn and to identify risk factors for hearing impairment. Chi-square test was used to investigate the difference between experimental and control group refer incidence. Results: A total of 1217 newborns was screened for hearing impairment of which 259 (21.28%) with one or more known risk factors for hearing impairment. The following risk factors for hearing impairment were identified during the study period: family history of permanent childhood hearing impairment in 42 (3.45%) newborns, prematurity in 39 (3.21%), low APGAR scores in 29 (2.40%), asphyxia in 31 (2.55%), hyperbilirubinemia in 41 (3.37%), admission of ototoxic medication (aminoglycosides) after birth in 155 (12.74%). Conclusion: There were many serious risk factors for hearing loss identified in this study. Identification of risk factors for hearing impairment in neonates is necessary because a follow up of the children with risk factors is very important.
Keywords: neonatal screening; hearing loss; otoacoustic emissions; follow up